Procurement Risk Management Practices and Service Delivery in Level Five Hospitals in Western Region, Kenya - Navalayo, Mary; Nyile, Erastus (International Journal of Supply Chain and Logistics, 2025)
Purpose: The general objective of this study was to examine the influence of procurement risk management practices on service delivery in Level five hospitals in Western region. Specifically the study assessed the influence of supplier diversification, supplier relationship management, strategic inventory management and procurement automation on service delivery in Level five hospitals in Western region. The study was guided by efficiency theory, resource dependence theory, transaction cost theory and diffusion of innovations theory. Methodology: The descriptive survey design was employed. This study targeted 116 stores and procurement staff from level five hospitals in Western region. These included Vihiga, Kakamega, Busia, TransNzoia and Bungoma County referral hospitals. Purposive sampling was used to select 86 staffs of the level five hospitals. Structured questionnaire were used to collect data. The study assessed validity through content, and construct validity. Reliability was evaluated using internal consistency of the instrument with the aid of Cronbach's Alpha coefficient. Data analysis involved descriptive statistics, including means and standard deviations. Additionally, inferential statistics, such as Pearson correlation and multiple regression were employed to analyze and test the hypotheses. Findings: The findings of the study revealed that all the independent variables had a significant positive influence on service delivery of level five hospitals. Specifically, the results showed that supplier relationship management had the greatest contribution to service delivery in the hospitals. Unique Contribution to Theory, Policy and Practice: The study, therefore, recommends that supplier diversification, relationships, inventory management, and automation be fully embraced to improve procurement performance and service delivery to hospital clients.